An Algorithm for Chebyshev Approximation by Rationals with Constrained Denominators - Gugat, Martin (Constructive Approximation, 1996)
The problem of rational approximation is facilitated by introducing both lower and upper bounds on the denominators. For a general fractional inf-sup problem with constrained denominators, a differential correction algorithm and convergence results are given. Numerical examples are presented. The proposed algorithm has certain advantages compared with the original differential correction method: not only upper but also lower bounds for the optimal value are computed, linear convergence is always guaranteed, and due to a different start convergence is more rapid.
UnivIS-Import:2015-03-05:Pub.1996.nat.dma.lama1.analgo
Keywords: 41A20; 65D15; 90C32; 90C34; Chebyshev approximation; Constrained denominators; Differential correction algorithm; Fractional programming; Rational approximation